An effective graph-based clustering technique to identify coherent patterns from gene expression data. (26th March 2012) - Priyadarshini, G.; Sarmah, R.; Chakraborty, B.; Bhattacharyya, D.K.; Kalita, J.K.
This paper presents an effective parameter-less graph based clustering technique (GCEPD). GCEPD produces highly coherent clusters in terms of various cluster validity measures. The technique finds highly coherent patterns containing genes with high biological relevance. Experiments with real life datasets establish that the method produces clusters that are significantly better than other similar algorithms in terms of various quality measures.